Men in nursing on television: exposing and reinforcing stereotypes. (4th September 2013) - Weaver, Roslyn; Ferguson, Caleb; Wilbourn, Mark; Salamonson, Yenna
Abstract Aims To describe the results of a study of images of men in nursing on television. Background Previous research has highlighted stereotypical images around nursing, such as the battle‐axe, naughty nurse and handmaiden. More recent research focuses on images of nurses who are men, because of the growing numbers of men in the nursing workforce. Given that negative images can harm recruitment and retention in the profession, it is important to interrogate how men in nursing are portrayed in popular culture. Representations on television are particularly critical to explore because of the medium's wide audience. Design Qualitative study. Methods Five American medical television programmes appearing between 2007 and 2010 were analysed for their construction of men in nursing: Grey's Anatomy, Hawthorne, Mercy, Nurse Jackie and Private Practice. Findings Men in nursing on television were portrayed in ways that engaged with explicit and implicit stereotypes. The men were often subject to questions about their choice of career, masculinity and sexuality and their role usually reduced to that of prop, minority spokesperson or source of comedy. Thus, rather contradictorily, although the programmes often sought to expose common stereotypes about men in nursing, they nonetheless often reinforced stereotypes in more implicit ways. Conclusion This research has implications for better understanding not only the status of nursing in our society but also for nursing practice and education and attracting more men to the profession.